Fishery and biology of penaeid prawn Parapenaeopsis maxillipedo Alcock along Chennai (Madras) coast - Subrahmanian, V Thankaraj (Indian Journal of Fisheries, 2011)
Parapenaeopsis maxillipedo supported a steadily increasing fishery along theChennai coast with the average annual catch of 326 t at the catch rate of 1.40kg/hr contributing 11.8% of prawn landings in 1990-'99. The catches were moreabundant in June-September and poor in summer months of April-May. Femaleswere relatively more in number and larger in size. The overall sex-ratio for 1992-'95 was 65.9 : 34.1% in favour of females. The length weight relationship was:Ln W = -3.9469 + 2.7077 Ln L for male and Ln W = -4.3493 + 2.8914 Ln L forfemale. The growth factors were: L°° = 108.0 mm and K = 2.61/year for malesL°° = 117.8 mm and K = 2.21/year for females. The species had a short life spanand only small fraction of the population could survive in the second year of life.Higher recruitment was recorded during February-March, June and September-October which was apparently linked to the greatbi spawning spells during June,October and February. The mortality rates were : Z = 7.4713, M = 4.3728 andF = 3.0985 for males and Z = 8.6939, M = 3.8301 and F = 4.8638 for females.These estimates gave an average exploitation rate of 0.49, that, with MSY of 304.7t against the average catch of 326.4 t, indicated that the species had been in thelevel of optimum fishing intensity during the study period.